The last Boleyn - Harper, Karen (Karen S.) (Three Rivers Press, 2006)
From the author of the bestselling "Elizabeth I" series comes the story of Mary Boleyn, whose beauty captured the hearts of two kings, and whose star rose and fell before that of her tragic sister Anne.